2019
DOI: 10.1111/dmcn.14403
|View full text |Cite
|
Sign up to set email alerts
|

Management of apnea in infants with trisomy 18

Abstract: This case series aimed to characterize the clinical features, management, and outcomes of apnea in infants with trisomy 18. Participants in this study were infants with trisomy 18 who were born alive and admitted to the neonatal intensive care unit in Kyushu University Hospital from 2000 to 2018. Retrospective analysis was performed on clinical data recorded in our department. Twenty‐seven infants with trisomy 18 were admitted to our hospital during the study period, of which 25 (nine males, 16 females) were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
(62 reference statements)
0
10
0
1
Order By: Relevance
“…A similar conclusion was drawn in another multi‐institutional study in which nonsurvivors of congenital heart surgery were all mechanically ventilated >2 days (Graham et al, 2004) prior to surgery. Yet, in a small case series of infants with T18 and known apnea, positive pressure ventilation was associated with improved survival (Taira et al, 2020). Fukasawa et al showed that some apneas are related to seizures, which improve with anti‐epileptic drugs (Fukasawa et al, 2015) and would otherwise not improve with invasive measures such as positive pressure ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion was drawn in another multi‐institutional study in which nonsurvivors of congenital heart surgery were all mechanically ventilated >2 days (Graham et al, 2004) prior to surgery. Yet, in a small case series of infants with T18 and known apnea, positive pressure ventilation was associated with improved survival (Taira et al, 2020). Fukasawa et al showed that some apneas are related to seizures, which improve with anti‐epileptic drugs (Fukasawa et al, 2015) and would otherwise not improve with invasive measures such as positive pressure ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 80% of infants with trisomy 18 suffer from one or more respiratory complications (Bruns & Campbell, 2014), including parenchymal lung disease as well as upper airway obstruction and pulmonary hypertension (Cereda & Carey, 2012). Apnea has been documented in 15%–56% of patients with trisomy 18, and 14% of these patients display tracheobronchial defects (Kosho et al, 2013; Pont et al, 2006; Taira et al, 2020). Despite the high prevalence of respiratory complications, the overall rate of tracheostomy is around 4%–8% for infants with trisomy 18 (Kosho et al, 2006; Nelson et al, 2012).…”
Section: Complications Of Trisomy 18mentioning
confidence: 99%
“…Controversy remains regarding whether aggressive respiratory or cardiac and digestive surgical interventions should be widely applied [1]. Recent studies report benefits for children with major malformations, with extended survival or home care [3][4][5][6]. DOI: 10.1159/000512922 Improved surgical techniques and understanding of the disease have led to more patients receiving medical attention, including cardiac surgery [7], thus influencing the outcomes for trisomy 18.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.1159/000512922 Improved surgical techniques and understanding of the disease have led to more patients receiving medical attention, including cardiac surgery [7], thus influencing the outcomes for trisomy 18. Currently, no comparable studies from Japan based on national data have reported the survival pattern in patients with trisomy 18 syndrome, despite numerous case reports and studies with longer postoperative survival times [4][5][6][8][9][10][11]. At least 1 hospital claims-based report showed that more patients receive invasive therapies, including surgery, than they did previously in Japan [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation